2021
DOI: 10.21083/partnership.v16i1.6189
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Labour of Public Library Work

Abstract: This study seeks to extend the research on the emotional labour of public library workers. Because emotional labour is a relatively new concept in library and information science research, researchers and practitioners need to better understand the emotional labour experiences of front-line workers in public libraries. A qualitative survey was distributed electronically to library workers in one Canadian province. Participants described meaningful experiences connecting with customers, but also identified majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Barniskis (2016: 114) describes how librarians’ roles have been reframed over time from ‘information experts to community advocates, teachers and as match-makers for people to meet one another and new ideas’. ‘Doing’ a social infrastructure requires staff to increasingly perform care, social work and ‘emotional labour’ (Rodger and Erickson, 2021; Wojciechowska, 2022), but also to demonstrate and legitimise the library’s values beyond its role as information provider as ‘convincing storytellers’ (Pilerot and Lindberg, 2018: 260) or ‘bookkeepers of social activities’ (Van Melik and Merry, 2021: 15). Consequently, librarians’ skills are also shifting, with present-day job advertisements for librarians unanimously mentioning communication, negotiation, collaboration and cultural intelligence as important requirements (Cherinet, 2018).…”
Section: Social Infrastructure and Community Librarianshipmentioning
confidence: 99%
“…Barniskis (2016: 114) describes how librarians’ roles have been reframed over time from ‘information experts to community advocates, teachers and as match-makers for people to meet one another and new ideas’. ‘Doing’ a social infrastructure requires staff to increasingly perform care, social work and ‘emotional labour’ (Rodger and Erickson, 2021; Wojciechowska, 2022), but also to demonstrate and legitimise the library’s values beyond its role as information provider as ‘convincing storytellers’ (Pilerot and Lindberg, 2018: 260) or ‘bookkeepers of social activities’ (Van Melik and Merry, 2021: 15). Consequently, librarians’ skills are also shifting, with present-day job advertisements for librarians unanimously mentioning communication, negotiation, collaboration and cultural intelligence as important requirements (Cherinet, 2018).…”
Section: Social Infrastructure and Community Librarianshipmentioning
confidence: 99%
“…Emmelhainz et al (2017) found that the Guidelines for behavioral performance of reference and information service providers located the success of reference transactions almost entirely in the behaviour rather than the competence of the librarian, while Julien and Genuis (2009) focused on the emotional labour components of information literacy instruction. Numerous studies (Matteson & Miller, 2013;Rodger & Erickson, 2021;Shuler & Morgan, 2013) have shown that the emotional labour required for library work can lead to increased burnout and decreased job satisfaction. While Joe (2019) suggests using mindfulness techniques to counter some of the strain of emotional labour, she avoids any discussion of its relation to the erasure of immaterial labour.…”
Section: Affective Librarianshipmentioning
confidence: 99%
“…Staff who represent racial and ethnic backgrounds underrepresented in the library profession may find themselves at odds with the expectations of staff and patron maps. This contributes to the emotional work of librarianship, which libraries often fail to acknowledge (Rodger & Erickson, 2021).…”
Section: Redesigning Mapsmentioning
confidence: 99%